2021
DOI: 10.1126/sciadv.abc6093
|View full text |Cite
|
Sign up to set email alerts
|

Usp11 controls cortical neurogenesis and neuronal migration through Sox11 stabilization

Abstract: The role of protein stabilization in cortical development remains poorly understood. A recessive mutation in the USP11 gene is found in a rare neurodevelopmental disorder with intellectual disability, but its pathogenicity and molecular mechanism are unknown. Here, we show that mouse Usp11 is expressed highly in embryonic cerebral cortex, and Usp11 deficiency impairs layer 6 neuron production, delays late-born neuronal migration, and disturbs cognition and anxiety behaviors. Mechanistically, these functions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Consistent with this possibility, phosphorylation by GSK3β induced ubiquitination and decreased overall Sox4 and Sox11 levels. Previous reports have shown that, in the neocortex, Sox11 cellular localization and protein stabilization are regulated by phosphorylation and ubiquitination, respectively, supporting that post‐transcriptional regulation of Sox11 is essential for its function in vivo (Balta et al , 2018a ; Balta et al , 2018b ; Chiang et al , 2021 ).…”
Section: Discussionmentioning
confidence: 77%
“…Consistent with this possibility, phosphorylation by GSK3β induced ubiquitination and decreased overall Sox4 and Sox11 levels. Previous reports have shown that, in the neocortex, Sox11 cellular localization and protein stabilization are regulated by phosphorylation and ubiquitination, respectively, supporting that post‐transcriptional regulation of Sox11 is essential for its function in vivo (Balta et al , 2018a ; Balta et al , 2018b ; Chiang et al , 2021 ).…”
Section: Discussionmentioning
confidence: 77%
“…SETDB1 also interacted with the proteasome component proteins PSMD2 and ADRM1, and USP11 (Fig. 5A), a deubiquitinase that is expressed primarily in the embryonic nervous system, regulates neurogenesis and neuronal migration and, accordingly, is upregulated in cancer cells and promotes cancer (31)(32)(33).…”
Section: Setdb1 Sustains a Regulatory Network Maintaining Neural Stem...mentioning
confidence: 99%
“…NanoLC−nanoESi-MS/MS analysis was performed on a Thermo UltiMate 3000 RSLCnano system connected to a Thermo Orbitrap Fusion mass spectrometer (Thermo Fisher Scientific, Bremen, Germany) equipped with a nanospray interface (New Objective, Woburn, MA, USA) and followed procedures as described previously [ 28 ]. Peptide mixtures were loaded onto a 75 μm ID, 25 cm length PepMap C18 column (Thermo Fisher Scientific) packed with 2 μm particles with a pore width of 100 Å and were separated using a segmented gradient in 120 min from 5 to 35% solvent B (0.1% formic acid in acetonitrile) at a flow rate of 300 nl/min.…”
Section: Methodsmentioning
confidence: 99%